INFLUENCE OF GENDER ON THE ONSET AND DURATION OF ROCURONIUM-INDUCED NEUROMUSCULAR BLOCK - Adamus, Milan; Koutna, Jirina; Gabrhelik, Tomas; Hubackova, Mariana; Janaskova, Eva (Biomedical papers, 2007)
Aims: To assess the influence of gender on the course of rocuronium-induced neuromuscular block following a single bolus dose of 2 * ED95 (0.6 mg kg-1).Methods: Following the ethics committee approval and informed consent, 245 patients (121 men, 124 women) scheduled for elective general surgery under TIVA with muscle relaxation were studied. After rocuronium 0.6 mg kg-1, the onset time for maximal depression of T1, clinical duration until 25 % recovery and recovery index (T1 from 25 to 75 %) were determined with TOF-Watch(R) SX accelerometric monitor. The data for male and female groups were compared with appropriate statistical tests (Student's unpaired t-test, Mann-Whitney Rank Sum Test and Fisher's exact test).Results: Men were significantly larger (p < 0.001) and heavier (p < 0.05) than women, but the body mass index was comparable (ns). The onset time was shorter in females [92.5 (SD 14.2) vs. 104.7 (12.2) s, p < 0.0001]. Clinical duration was increased in females [43.1 (7.9) vs. 31.3 (5.5) min; p < 0.0001], while the recovery index was identical in both groups [14.7 (5.0) min in females and 14.8 (4.0) min in males; ns].Conclusions: Women are more sensitive than men to the dose 0.6 mg kg-1 of rocuronium. Under the study conditions described, the onset time was shortened and the clinical duration increased in female patients. This suggests that the routine dose of rocuronium should be reduced in women.
Keywords: Neuromuscular block/Gender/Rocuronium/Clinical duration/Onset time/Recovery index